Answer:
![\frac{(x+3)^2}{36^{}}-((y-2)^2)/(16)=1](https://img.qammunity.org/2023/formulas/mathematics/college/uswd8y9qnsagtnlgetyvzeq6c7grxbqacm.png)
Step-by-step explanation:
The standard form of the equation of a hyperbola with center (h,k) and transverse axis parallel to the x-axis is:
![((x-h)^2)/(a^2)-((y-k)^2)/(b^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/p9z9gumo8hk2p84uo05au4dcim97672l9q.png)
Where:
• The length of the transverse axis = 2a
,
• The length of the conjugate axis = 2b
![\begin{gathered} \text{Centre,}(h,k)=(-3,2) \\ \text{The length of the transverse axis, 2a = 12 units}\implies a=(12)/(2)=6 \\ \text{The length of the conjugate axis, 2b = 8 units}\implies b=(8)/(2)=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k4gs5tozvwou49jc7hjmpqfrxi2tdjb7qy.png)
Therefore. the equation of the hyperbola is:
![\begin{gathered} ((x-(-3))^2)/(6^2)-((y-2)^2)/(4^2)=1 \\ \implies\frac{(x+3)^2}{36^{}}-((y-2)^2)/(16)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/of0sdr0ec4hprwdpy0pdmbmaupw4l9y28w.png)